Peerwise provides significant academic benefits to biological science students across diverse learning tasks, but with minimal instructor intervention. Issue 5 (26th June 2014) - McQueen, H. A.; Shields, C.; Finnegan, D. J.; Higham, J.; Simmen, M. W.
Abstract We demonstrate that student engagement with PeerWise, an online tool that allows students to author and answer multiple‐choice questions (MCQs), is associated with enhanced academic performance across diverse assessment types on a second year Genetics course. Benefits were consistent over three course deliveries, with differential benefits bestowed on groups of different prior ability. A rating scheme, to assess the educational quality of students' questions, is presented and demonstrates that our students are able intuitively to make such quality assessments, and that the process of authoring high quality questions alone does not explain the academic benefits. We further test the benefits of providing additional PeerWise support and conclude that PeerWise works efficiently with minimal intervention, and can be reliably assessed using automatically generated PeerWise scores. © 2014 by The International Union of Biochemistry and Molecular Biology, 42(5):371–381, 2014.